2019
DOI: 10.3390/ijms20246152
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Mediated Activation of Natural Autoantibody Producing B Cell Subpopulations in an Autoimmune Disease Model

Abstract: Altered expression and function of the Toll-like receptor (TLR) homologue CD180 molecule in B cells have been associated with autoimmune disorders. In this study, we report decreased expression of CD180 at protein and mRNA levels in peripheral blood B cells of diffuse cutaneous systemic sclerosis (dcSSc) patients. To analyze the effect of CD180 stimulation, together with CpG (TLR9 ligand) treatment, on the phenotype defined by CD19/CD27/IgD/CD24/CD38 staining, and function (CD69 and CD180 expression, cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…CD180 was originally defined as a B cell surface molecule mediating activation and proliferation [ 33 ] and was later described as a TLR homolog expressed by dendritic cells and macrophages. We previously demonstrated that the expression of CD180 in anti-CD180 activated B cells was decreased [ 12 ], supporting the theory proposed by Chaplin at al. [ 34 ] that CD180 can be internalized after ligation, thus decreased level of CD180 could reflect the enhanced activation of B cells via CD180.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…CD180 was originally defined as a B cell surface molecule mediating activation and proliferation [ 33 ] and was later described as a TLR homolog expressed by dendritic cells and macrophages. We previously demonstrated that the expression of CD180 in anti-CD180 activated B cells was decreased [ 12 ], supporting the theory proposed by Chaplin at al. [ 34 ] that CD180 can be internalized after ligation, thus decreased level of CD180 could reflect the enhanced activation of B cells via CD180.…”
Section: Discussionsupporting
confidence: 85%
“…We previously reported that the CD180 protein expression of B cells was significantly lower in early dcSSc than in HC [ 12 ]. In this study, we sought to investigate the TLR4 and C3 protein expression of dcSSc and HC B cells with flow cytometry, but the statistical analysis of the mean fluorescence intensity (MFI) values of C3 and TLR4 labeling of B cells was not applicable due to the high standard deviations of data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We might then find a new phenomenon in B cells with stimulation using αRP105-TM because, to our knowledge, stimulation such as trogocytosis via RP105 has never been conducted. In addition, we expect to obtain insight into the natural RP105 ligand, which has not yet been identified ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The molecule RP105 (CD180) is an orphan Toll-like receptor (TLR) ( 5 , 6 ). It has a short cytoplasmic tail that lacks the Toll-IL-1 receptor (TIR) domain, which is necessary for mediating TLR signaling ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%